Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used.

Consider the function.

[tex]\[ f(x) = 2x - 6 \][/tex]

Match each transformation of [tex]\( f(x) \)[/tex] with its description.

[tex]\[ g(x) = 2x - 2 \][/tex]
[tex]\[ \begin{array}{l}
g(x) = 8x - 6 \\
g(x) = 8x - 24 \\
g(x) = 8x - 4 \\
g(x) = 2x - 14 \\
g(x) = 2x - 10 \\
\end{array} \][/tex]

[tex]\[
\begin{array}{l}
\text{compresses } f(x) \text{ by a factor of } \frac{1}{4} \text{ toward the } y\text{-axis} \quad \square \\
\text{stretches } f(x) \text{ by a factor of 4 away from the } x\text{-axis} \quad \square \\
\text{shifts } f(x) \text{ 4 units right} \quad \square \\
\text{shifts } f(x) \text{ 4 units down} \quad \square \\
\end{array}
\][/tex]


Sagot :

Alright, let's take each transformation of [tex]\( f(x) = 2x - 6 \)[/tex] one by one and match it with the descriptions provided:

1. Compresses [tex]\( f(x) \)[/tex] by a factor of [tex]\( \frac{1}{4} \)[/tex] toward the [tex]\( y \)[/tex]-axis:

Compressing [tex]\( f(x) = 2x - 6 \)[/tex] by a factor of [tex]\( \frac{1}{4} \)[/tex] toward the [tex]\( y \)[/tex]-axis means we multiply the coefficient of [tex]\( x \)[/tex] by 4.

[tex]\[ f\left(\frac{x}{4}\right) = 2\left(\frac{x}{4}\right) - 6 = \frac{1}{2}x - 6 \quad (\text{This transformation is not obtained directly from the provided functions, hence discard it}) \][/tex]

Alternatively, compress the entire function:

[tex]\( g(x) = \frac{f(x)}{4} = \frac{2x-6}{4} = \frac{1}{2}x - 1.5 (\text{none match, another discard}) \)[/tex]

The correct function provided for this case would be:

[tex]\( g(x) = 8x - 24 \)[/tex]

2. Stretches [tex]\( f(x) \)[/tex] by a factor of 4 away from the [tex]\( x \)[/tex]-axis:

Stretching [tex]\( f(x) = 2x - 6 \)[/tex] by a factor of 4 means we multiply the entire function by 4:

[tex]\[ g(x) = 4(2x - 6) = 8x - 24 \][/tex]

The function [tex]\( g(x) = 8x - 24 \)[/tex] matches this transformation.

3. Shifts [tex]\( f(x) \)[/tex] 4 units to the right:

Shifting the function to the right by 4 units means we replace [tex]\( x \)[/tex] by [tex]\( x - 4 \)[/tex]:

[tex]\[ f(x - 4) = 2(x - 4) - 6 = 2x - 8 - 6 = 2x - 14 \][/tex]

The function [tex]\( g(x) = 2x - 14 \)[/tex] matches this transformation.

4. Shifts [tex]\( f(x) \)[/tex] 4 units down:

Shifting the function downward by 4 units means we subtract 4 from the whole function:

[tex]\[ f(x) - 4 = (2x - 6) - 4 = 2x - 10 \][/tex]

The function [tex]\( g(x) = 2x - 10 \)[/tex] matches this transformation.

By matching the transformations and descriptions:
- Compresses [tex]\( f(x) \)[/tex] by a factor of [tex]\( \frac{1}{4} \)[/tex] toward the [tex]\( y \)[/tex]-axis: [tex]\( \(g(x) = 8x-24\)[/tex]
- Stretches [tex]\( f(x) \)[/tex] by a factor of 4 away from the [tex]\( x \)[/tex]-axis: [tex]\( \(g(x) = 8x-24\)[/tex]
- Shifts [tex]\( f(x) 4 \)[/tex] units right: [tex]\( \(g(x) = 2x-14\)[/tex]
- Shifts [tex]\( f(x) 4 \)[/tex] units down: [tex]\( \(g(x) = 2x-10\)[/tex]